Distractor Dwelling, Skipping, and Revisiting Determine Target Absent Performance in Difficult Visual Search - Horstmann, Gernot; Herwig, Arvid; Becker, Stefanie I. (Frontiers in Psychology, 2016)
Some targets in visual search are more difficult to find than others. In particular, a target that is similar to the distractors is more difficult to find than a target that is dissimilar to the distractors. Efficiency differences between easy and difficult searches are manifest not only in target-present trials but also in target-absent trials. In fact, even physically identical displays are searched through with different efficiency depending on the searched-for target. Here, we monitored eye movements in search for a target similar to the distractors (difficult search) versus a target dissimilar to the distractors (easy search). We aimed to examine three hypotheses concerning the causes of differential search efficiencies in target-absent trials: (a) distractor dwelling (b) distractor skipping, and (c) distractor revisiting. Reaction times increased with target similarity which is consistent with existing theories and replicates earlier results. Eye movement data indicated guidance in target trials, even though search was very slow. Dwelling, skipping, and revisiting contributed to low search efficiency in difficult search, with dwelling being the strongest factor. It is argued that differences in dwell time account for a large amount of total search time differences.